KONTRIBUSI POWER OTOT TUNGKAI TERHADAP KEMAMPUAN TENDANGAN SABIT SISWA EKSTRAKURIKULER PENCAK SILAT SMA PGRI KOTA PEKANBARU - Tengku Febbi Romadhan Putra; Slamet Slamet; Aref Vai Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: The problem of this research is based on the observation of the students of extracurricular pencak silat in SMA PGRI Kota Pekanbaru it is seen that the low ability of crescent sickle which they do this indicates caused by the student's limb muscle muscle which is still weak or not maximal, so that the crescent done less powerful. in addition there are still students who are still less precise in performing sickle kick movement techniques. Inadequate muscle limb power of students will also affect the ability of sickle kick done by students. The coordination of motion possessed by the students is also not maximized, it will affect the ability of the sickle kick, the kick will be easily anticipated by the opponent by doing the rebuttal, and even facilitate the opponent to counterattack quickly and suddenly. The purpose of this study is to determine the contribution of leg muscle power to the ability of sickle crescent students extracurricular Pencak Silat SMA PGRI Kota Pekanbaru. This type of research is correlational, Corelational is a statistical tool, which can be used to compare the measurement results of two different variables. The population in this study were all students extracurricular Pencak Silat SMA PGRI Kota Pekanbaru who actively participated in pencak silat training which amounted to 16 students. The sampling technique, using total sampling technique. The result of research analysis showed that rhitung = 0,519 and at 5% significant level found rtabel = 0,497 with strong relationship level category. Keywords: Limb muscle power, Abilities of sickle kick